Association between variation of circulating 25-OH vitamin D and methylation of secreted frizzled-related protein 2 in colorectal cancer - Boughanem Lakhal, Hatim; Cabrera-Mulero, Amanda; Hernández Alonso, Daniel; Clemente-Postigo, María Mercedes; Casanueva, Felipe F.; Tinahones-Madueño, Francisco José; Morcillo Espina, Sonsoles; Crujeiras Martínez, Ana Belén; Macías-González, Manuel (Springer Nature, 2020)
Colorectal cancer (CRC) results from the accumulation of epigenetic and genetic changes in colon cells during neoplasic transformation, which the activation of Wingless (Wnt) signaling pathway is a common mechanism for CRC initiation. The Wnt pathway is mainly regulated by Wnt antagonists, as secreted frizzled-related protein (SFRP) family. Indeed, SFRP2 is proposed as a noninvasive biomarker for CRC diagnosis. Vitamin D also antagonizes Wnt signaling in colon cancers cells. Several studies showed that vitamin D was able to alter DNA methylation, although this mechanism is not yet clear. Therefore, the aim of this study was to find an association between circulating 25-OH vitamin D (30th percentile of vitamin D) and the SFRP2 methylation.
Keywords: Colon - Cáncer; Recto - Cáncer; SFRP2 methylation; 25-OH vitamin D; Colorectal cancer; Neoadjuvant treatment